Flood Risk in Char Community: An Evidence‐Based Study in Bangladesh - Md Mostafizur Rahman; Mst. Nusrat Jahan Suchi; Abir Mohd Shakib Shahide; Md. Tanvir Hossain; Edris Alam; Md Kamrul Islam (Journal of Flood Risk Management, 2025)
ABSTRACT This study evaluates the flood risk of households in the flood‐prone Char areas of Dewanganj, Jamalpur, Bangladesh, focusing on sociodemographic factors, vulnerability, flood exposure, and capacity. Using survey data from 400 households, we found a predominance of male‐headed households, a high reliance on wage labor, and widespread substandard housing, all contributing to flood risk. The findings reveal a rise in flood frequency and home inundation; nearly all respondents (99.75%) confirm worsening flood conditions, indicating a long‐term climate trend rather than isolated events. Vulnerabilities are further heightened by low education levels (60.75% with no formal education), high poverty rates (98.75% below the national income average), and limited access to critical resources like durable housing and flood preparedness training. Regression analyses indicate significant associations between flood risk and factors like age, income source, and housing type (female‐headed households: p < 0.001, β = 0.06; age groups 36–45 and 46–55: p < 0.001, β = 0.07, and β = 0.11, respectively). The study highlights the need for targeted interventions, with the most critical recommendation being the improvement of housing resilience, especially for vulnerable groups such as female‐headed households and those in temporary structures. Enhanced flood forecasting, resilient infrastructure, and community‐based training programs are also essential for reducing flood risk and increasing adaptive capacity. Our findings provide actionable insights for policymakers and NGOs to develop tailored flood resilience strategies, offering a foundational model for flood‐prone communities across Bangladesh.